Myst1 Acetyltranferase Regulates Pax7 Function - Rosembert, Tabitha (Université d'Ottawa / University of Ottawa, 2018)
Pax7 is essential for the function of muscle satellite cells. It was previously determined that Pax7 methylation is essential for its transcriptional activity and function in satellite cells. We investigated whether Pax7 displays other post-translational modifications playing a role in its function. By mass spectrometry using immunoprecipitated FLAG-Pax7, we identified two lysine residues (K105 and K193) within the Pax7 protein that are acetylated. Pax7 transcriptional activity was monitored using a luciferase reporter under the control of Myf5, a Pax7 target gene. Treatment with Trichostatin A, a histone deacetylase inhibitor, increased significantly luciferase activity, but this activity was progressively loss when the created Pax7 mutants (K105R, K193R) were introduced. This suggests that acetylation plays a role in Pax7 transcriptional activity. To identify the acetyltransferase modulating Pax7 activity, we used a candidate approach. Myst1 is expressed in muscle satellite cells. Myst1 is known for its interaction with Wdr5 and MLL1/2, a known Pax7 partner. We detected an interaction between Pax7 and Myst1 by co-immunoprecipitation in fibroblasts and in primary myoblasts. Myst1 knockdown decreases Pax7 acetylation status suggesting Myst1 as Pax7’s acetylase. Myst1 siRNA knockdown negatively impacts many Pax7’s target genes as well as primary myoblast proliferation. Moreover, primary myoblasts treated with siMyst1 express higher levels of MyoD. In satellite cells Myst1 reduction through siRNA knockdown significantly reduces satellite cells progenitor expansion as well as increases MyoD expression. In all, Myst1 modulating Pax7 activity through acetylation represents a novel mechanism in muscle stem cell biology.
Keywords: Stemcells; Myogensis; PTM